046 MR-based intramuscular fat fraction assessment in hereditary sensory neuropathy type 1. (23rd August 2021) - Barnes, Stephanie L; Chan, Michael V; Morris, Stephen; Nicholson, Garth A
Abstract : Objectives: Hereditary sensory neuropathy type 1 (HSN1) is a rare progressive neuropathy characterised by profound sensory dysfunction, often accompanied by significant weakness. Muscle magnetic resonance (MR) imaging with determination of intramuscular fat accumulation has been proposed as a marker of progression in this condition and we aimed to investigate this further. Methods: Calf-level muscle MR images were acquired longitudinally over three years in patients with genetically confirmed HSN1 due to SPTLC1 and SPTLC2 mutations. These patients were part of a larger trial of L-serine supplementation as a candidate therapy and MR images were acquired at baseline and while on treatment. Individual muscles and muscle groups were manually segmented at two cross-sectional levels in the proximal calf. Intramuscular fat accumulation and muscle atrophy were assessed. Results: Detailed MR analysis was performed in a preliminary series of three patients. We demonstrated an average annual change in MR-based intramuscular calf fat fraction of 3.2%, 1.0% and 3.7% at a cross-sectional level 130mm below the tibial plateau and 2.0%, 0.6% and 1.2% at a cross-sectional level 25% of the tibial plateau-medial malleolus distance. The degree of muscle atrophy did not significantly change. There appeared to be ongoing progression of disease during this short duration of L-serine supplementation. Conclusion: MR-based intramuscular calf fat fraction can be used to monitor progression in HSN1 and has potential utility in clinical trials. Technical limitations to this technique may be overcome using volumetric imaging with automated muscle segmentation in the future. Further investigation of L-serine supplementation is required.